Epidemiology of intrauterine fetal death in Dhaka National Medical College Hospital - Bakshi, Lipy; Hoque, Samira; Tanjin, Farhana; Dey, Sukla; Bakshi, Mithun (Bangladesh Medical Journal, 2017)
Intrauterine fetal death (IUFD) and still births is a tragic event for the parents and an important cause of perinatal mortality. This retrospective study study was conducted in the department of Obstetrics and Gynecology of Dhaka National Medical College Hospital from January 2015 to June 2016 with the intention to understand the incidence, socio-epidemiological and etiological factors of intrauterine fetal death (IUFD). A total of 1838 pregnancies were studied retrospectively during the study period & out of them 48 were IUFDs. Ante partum and intra partum events leading to fetal demise were recorded, socio-demographic and clinical characters were noted. there were 1838 deliveries . The incidence of prenatal loss was 26 per 1000 live births. Despite advances in diagnostic and therapeutic modalities the rate of IUD is unacceptably high. Socio-cultural background, lack of adequate antenatal care and inaccessible health care are some of the reasons that predispose women to IUFD. Majority of fetal wastage can be prevented with universal and improved antenatal care. Bangladesh Med J. 2016 Sep; 45 (3): 131-133